That sugar film [videorecording (DVD)] - Gameau, Damon; Jackman, Hugh; Fry, Stephen, 1957- (Samuel Goldwyn Films, 2015)
An expectant father undertakes a perilous/delicious mission to see what the hidden sugars in seemingly healthy products can do to both his body and brain chemistry in this eye-opening new documentary that must be seen to be believed.